Deteksi Begomovirus pada Cabai Secara Cepat melalui Isolasi Genom DNA - Sri Sulandari; Rusmilah Suseno; Sri Hendrastuti Hidayat; Soemartono Sosromarsono; Jumanto Harjosudarmo (Universitas Gadjah Mada, 2007)
Pepper yellow leaf culr disease has been widely spreading in Indonesia, especially in Special Province of Yogyakarta and Central Java since 2000. The disease is difficult to control because its fast spreading over in the field by the vector. To prevent epidemic of the disease, early detection method of the causal agent is needed. The aim of the research was to detect the causal agent of the pepper yellow leaf curl disease by isolating the DNA genome. Using the Guanidine-alkaline method, two specific fragments of the DNA were produced approximately at 2600 bp and 1600 bp. The DNA fragments were similar with the DNA genome of Begomovirus. The method applied in this study is faster and easier for early detection of the Begomovirus in infected crop than detection by the Polymerase chain reaction (PCR).